The moderation of age on the relationship between entrepreneurial role models and entrepreneurship: evidence from a transition economy - Nguyễn, Thị Lành (Taylor & Francis, 2024)
This study examines the influence of entrepreneurial role models on an individual’s decision to become self-employed and how age moderates this relationship. We use a dataset of 8000 individuals from the Global Entrepreneurship Monitor (GEM 2013–2017) and apply logit regressions to assess this relationship. the findings confirm a significantly positive effect of entrepreneurial role models on the decision to be entrepreneurs among vietnamese adults. Furthermore, the positive influence of entrepreneurial role models on self-employment is weaker for older individuals than for younger generations. results provide implications for policies and practices to nurture entrepreneurship.